Analisis Yuridis Putusan Perkara No. 36/Pdt.G/2023/PN Pdg Tentang Gugatan Parate Executie Hak Tanggungan Atas Dasar Wanprestasi Terhadap Debitur - Maridus Maridus; Darwan Suryadi (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
Banking is one of the economic sectors that is vital for economic growth, but banking is often faced with financial risks caused by high non-performing loans. In case Number: 36/Pdt.G/2023/PN Pdg explains that the creditor will conduct an auction of the Mortgage Right object to guarantee debt repayment. The problem started when the plaintiff neglected to fulfill his credit collectibility obligations, classified as a